(untitled) (Modern education and development, 2025)
The acquisition of vocabulary is essential for achieving proficiency in English as a Foreign Language (EFL), particularly at the university level where students are expected to master both general and academic language. This study investigates and compares the effectiveness of direct and indirect vocabulary learning strategies (VLS) employed by EFL university students. Direct strategies involve explicit learning techniques such as memorization, word lists, and translation, while indirect strategies include contextual inference, language exposure, and social interaction. Using a mixed-method approach involving surveys, vocabulary tests, and classroom observations, this research explores how these strategy types influence vocabulary acquisition and retention. The findings indicate that while direct strategies often lead to faster short-term vocabulary gains, indirect strategies contribute more significantly to long-term retention and contextual usage. Furthermore, the study highlights the importance of integrating both types of strategies to accommodate diverse learner preferences and enhance vocabulary development. These insights offer practical implications for EFL instructors, curriculum designers, and learners aiming to improve vocabulary acquisition in university contexts.